Impact of volcanic eruptions on heavy metal contamination in the food chain - Samuele Pulze; Noemi Presti; Aniello Anastasio (Italian Journal of Food Safety)
This work aims to assess the risk of heavy metal contamination of volcanic origin in the agri-food chain, describing the potential danger to human health. Volcanic phenomena lead to the environmental presence of contaminants, including heavy metals, which influence our ecosystems, food, and health. Opinions have been expressed regarding the presence of heavy metals in our diet and the potential risk of food contamination following volcanic eruptions. Regulation (EU) 915/2023 does not reference the sanctions that would be applied if food products with analytical values exceeding the established tolerance limits for heavy metals were marketed. Legislative Decree No. 18 of February 23, 2023, while providing a sanctions framework, is not specific to the exceedance of maximum limits for heavy metals in water intended for human consumption; it is plausible to apply the Penal Code (Articles 444 and 452) and Law No. 283 of April 30, 1962. The effect of volcanic eruptions seems to play a residual role in heavy metal contamination in food supply chains, considering that their presence is quantified in trace amounts. Given that a limited number of active volcanoes have been monitored for heavy metal emissions and that data regarding the contribution of volcanic activity is lacking, there are still too many missing pieces to conduct a realistic risk assessment of the impact volcanic activity has on the food chain. In conclusion, the 2022 Environmental Data Yearbook from the Higher Institute for Environmental Protection and Research indicates that Italy has achieved the goals set internationally by the Aarhus Convention.